PERANCANGAN MEDIA BUKU POP-UP CERITA RAKYAT RAMBUN PAMENAN SUMATERA BARAT - Masykura Safitri Hadi, Drs. Syafwan, M.Si., Ir. Drs. Heldi, M.Si., Ph.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The objective of this design is to design the pop-up book forRambun Pamenan Folklore of West Sumatera as communicative andeducative media in order to conserve the culture value for children as thetarget audience. The data is analyzed with SWOT method (strength,weakness, opportunitues and threat). Data collection is done by doingobservation method, interview and documentation. Pop-up book ofRambun Pamenan was designed by using the theory of visualcommunication design, children psychology, folklore, media, book, popupbook, illustration, color, layout and typography. Beside the design ofpop-up book as the prime media, it is also supported by other media suchas poster, x-banner, t-shirt, hat, pin, drawstring pouch, and stickerKey search: Meda, Pop-up Book, Rambun Pamenan folklore